Urban Vindkraft - Brunk, Ann-Charlotte (2010)
This paper aims to explore the phenomenon urban wind energy, its visual effect on built environment and the factors that affect the opinion towards new elements in the city. A place study of the city Gävle serves as a complement to the theoretical part of the paper.